2015
DOI: 10.15537/smj.2015.5.10785
|View full text |Cite
|
Sign up to set email alerts
|

A review of the therapeutic effects of using miswak (Salvadora Persica) on oral health

Abstract: Miswak is a traditional chewing stick prepared from the roots, twigs, and stem of Salvadora persica and has been used as a natural method for tooth cleaning in many parts of the world for thousands of years. A number of scientific studies have demonstrated that the miswak (Salvadora persica) possesses antibacterial, anti-fungal, anti-viral, anti-cariogenic, and anti-plaque properties. Several studies have also claimed that miswak has anti-oxidant, analgesic, and anti-inflammatory effects. The use of a miswak h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
108
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(134 citation statements)
references
References 47 publications
3
108
0
7
Order By: Relevance
“…33 Al-Salman et al 38 suggested that 10% of water extract of miswak is an effective antimicrobial when utilized as a root canal irrrigant with necrotic pulp. Due to its good antimicrobial activity 39 and low level of cytotoxicity, it can replace sodium hypochlorite and CHX for a root canal irrigant. It can be used even in primary teeth as irrigant and is safer than sodium hypochlorite.…”
Section: Salvadora Persica (Miswak)mentioning
confidence: 99%
“…33 Al-Salman et al 38 suggested that 10% of water extract of miswak is an effective antimicrobial when utilized as a root canal irrrigant with necrotic pulp. Due to its good antimicrobial activity 39 and low level of cytotoxicity, it can replace sodium hypochlorite and CHX for a root canal irrigant. It can be used even in primary teeth as irrigant and is safer than sodium hypochlorite.…”
Section: Salvadora Persica (Miswak)mentioning
confidence: 99%
“…Therefore, the need to address questions regarding microorganism adherence and biofilm development is crucial. 3,4 A previous study has shown miswak to be similar or even more effective than toothbrushing in plaque removal. 5,6 In addition, miswak has been shown to exhibit a higher reduction in gingivitis provided that professional instructions have been given.…”
Section: Introductionmentioning
confidence: 99%
“…Then, it is used until it loses its taste and odor. [3][4][5] Gentle, circular movements should be used to massage the gingiva and to avoid any damage and possible gingival recession. 4,5 On completion of tooth cleaning, the used bristles are trimmed away and new ones are prepared by further chewing.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations